Interstitial water geochemistry results of IODP Hole 389-M0101A - Webster, Jody M; Ravelo, Ana Christina; Grant, Hannah; Stewart, Margaret S; Rydzy, Marisa; Le Ber, Erwan; Allison, Nicola; Asami, Ryuji; Boston, Brian; Braga, Juan-Carlos; Brenner, Logan; Chen, Xuefei; et al. (PANGAEA, 2025)
Results of interstitial water (IW) geochemistry analyses from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The offshore phase of this expedition took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai'i, USA, followed by the onshore phase from 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. Sampling for IW geochemistry took place offshore immediately upon core recovery where soft sediments where recovered and using Rhizon samplers. The Rhizone samplers were left in the sediment for extraction of interstitial water for a minimum of 2 hours, aiming at drawing enough IW per sample from the core sections to fulfill the IODP standard IW sample splitting plan that included as many eight fractions. In addition to IW from the core sections, reference samples of the surface seawater (SSW) were collected (s. dataset "Surface seawater geochemistry results of IODP Expedition 389 (Hawaiian Drowned Reefs)"). Quality flag "#0" indicates the measurements' result was below detection limit. For further methodological information see methods chapter in Webster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025
Keywords: central Pacific; Coral Reef; Earth climate feedbacks; Earth history tipping points; Expedition 389; Hawaiian Drowned Reefs; Hawaiian geology; International Ocean Discovery Program (IODP); MMA Valour; Paleoclimate; sea level; volcanic